Purification, characterization and mode of action of plantaricin K25 produced by Lactobacillus plantarum - Wen, L.S.; Philip, K.; Ajam, N. (Elsevier, 2016)
The aim of this study was to elucidate the mode of action of a novel bacteriocin with low molecular weight that was isolated, purified and characterised from Lactobacillus plantarum K25 and found propagating in kimchi samples. This antimicrobial peptide, named plantaricin K25 was recovered from the producer cells by using adsorption-desorption method and purified by high-performance liquid chromatography. It exhibited a broad spectrum of inhibitory activity against both Gram-positive and Gram-negative bacteria. Plantaricin K25 retained bioactivity when exposed to high temperature (121 °C) and remained stable at pH values ranging from 2 to 8. This peptide was partially inactivated by proteinase and pronase and fully degraded by peptidase and trypsin. It remained active after being treated with lipase, amylase, catalase and certain detergents. Based on Tris-Tricine SDS-PAGE of purified bacteriocin, the molecular weight was estimated at 2 kDa. MALDI-TOF mass spectrophotometry showed that the precise molecular weight of the peptide was 1772 Da. Plantaricin K25 showed to be a pore-forming bacteriocin capable of permeabilising the cytoplasmic membrane of targeted bacterial cells. When viewed under SEM and TEM, cell membranes of Bacillus cereus appeared to collapse and disrupt after exposure to the bacteriocin. Plantaricin K25 inhibited the growth of B. cereus cultivated in mul-kimchi with reduction of viable cell counts compared to the control sample. Genome sequencing using Illumina MiSeq showed absence of virulence genes in strain K25 indicating its basic biosafety property. These results suggest that plantaricin K25 can be a suitable alternative to other preservatives used to improve the shelf life of many perishable food products.